Uma nova fronteira da revolução industrial 4.0: smart materials - Alves, Caio Cezar Santos Barbosa (Universidade Federal de São Carlos, 2022)
Throughout economic and productive development, we went through some revolutions that have changed the course of society and productive means. We are currently undergoing a fourth industrial revolution, which unites physical, digital and even biological means. One of the gears of this system is the use of intelligent devices, such as sensors and actuators, which preferably manage to generate autonomy in the operation of systems and equipment, which are the smart materials. Within this context, the present working paper, through a bibliographic review, unraveled a summary of the main basic questions, and the physicochemical mechanisms for their functioning, composition factors, processing, properties and applications, as well as future trends. Such classes of materials are: alloys with memory effect, piezoelectric, electrostrictors, optical fibers and magnetostrictors.
A new frontier of the industrial revolution 4.0: smart materials
Keywords: Indústria 4.0; Piezoelétricos; Eletrostritores; Fibras Ópticas; Magnetostritivos; Smart Materials; Industry 4.0; Piezoelectric; Electrostrictors; Optical Fibers; Magnetostrictors; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::MATERIAIS NAO METALICOS